The Media and Communications Study Skills Student Guide - Specht, Doug (University of Westminster Press, 2019)
"All the tips, ideas and advice given to, and requested by, MA students in Media and Communications, are brought together in an easy-to-use accessible guide to help students study most effectively. Based upon many years of teaching study skills and hundreds of lecture slides and handouts this introduction covers a range of general and generic skills that the author relates specifically towards media and communications studies. As well as the mechanics of writing and presentations, the book also shows how students can work on and engage with the critical and contemplative elements of their degrees whilst retaining motivation and refining timekeeping skills. Of course the nuts and bolts of reading, writing, listening, seminars and the dreaded dissertation and essays are covered too. In addition advice on referencing, citation and academic style is offered for those with concerns over English grammar and expression. Aimed primarily at postgraduate students, there is significant crossover with undergraduate work, so this book will also prove of use to upper level undergraduate readers whether using English as a first or second language."